PROPIEDADES PSICOMÉTRICAS DEL CUESTIONARIO DE AGRESIÓN EN DOS MUESTRAS DIFERENTES DE HIDALGO, MÉXICO - Matías, Oscar Mariano Pérez; Andrade, Norma Angélica Ortega; Arenas, Alicia Berenice Rincón; Cruz, Rubén García; Ramírez, Mucio Alejandro Romero (European Scientific Journal, ESJ, 2013)
Aggression is defined as a multifactorial phenomenon in which the person has a propensity toward hostile thoughts and negative affect, and preparing to attack physically and verbally (Buss and Perry, 1992) . In assessing this construct, the Aggression Questionnaire of Buss and Perry (1992) represents one of the most used worldwide due to rigor in their development and the existing evidence on their effectiveness in detecting aggression in general populations adulthood. The present study aims to evaluate the psychometric properties of the Spanish version of the Aggression Questionnaire in two samples of inhabitants of the state of Hidalgo in Mexico, the first of which consists of 300 people from the general population with an age range of 20-60 years and the second by 300 college students from the University of the State of Hidalgo with an age range of 17-27 years. The results indicate that this instrument is valid and reliable for use in Mexican population in adulthood, however differences were found with regard to the composition of the items between the two samples obtained.